Pulsating auroral electron flux modulations in the equatorial magnetosphere. Issue 8 (5th August 2013) - Jaynes, A. N.; Lessard, M. R.; Rodriguez, J. V.; Donovan, E.; Loto'aniu, T. M.; Rychert, K.
Abstract : [1] In this study, we present the first in situ continuous measurements of electron flux modulations in the near‐equatorial magnetosphere correlated with pulsating aurora (PA) observations. The contested conjecture that the source of these electrons originates near the equator, made decades ago using sounding rocket data, has now been confirmed using this data. We compared the frequencies of equatorial electron flux pulsations and PA luminosity fluctuations at their ionospheric footprint, using simultaneous satellite‐ and ground‐based data from GOES 13 and Time History of Events and Macroscale Interactions during Substorms (THEMIS) instrumentation. Observations of PA were obtained on 15 March 2008 using a THEMIS All‐Sky Imager (ASI) located in northern Canada. The field line footprint of the geostationary GOES 13 satellite, mapped down to the ionosphere at ∼100 km, falls within the field‐of‐view of the ASI. We examined electron flux data from the Magnetospheric Electron Detector (MAGED) on GOES 13, in the energy range of 30 to 50 keV, by computing an array of the correlation coefficients between the pixel luminosity for each individual pixel of the ASI images and the flux measurements at the satellite. The results reveal a direct correlation between diffuse luminosity fluctuation periods near the ground and particle pulsation periods. The time variance between the two data sets was examined in order to explore the validity of the equatorial source region premise. The resulting time lag of < 1 s in the PA measurements is consistent with this claim. We also report on a preliminary quantification of the loss cone using the MAGED telescope response functions. Key Points: The source of PA modulations lies in the near‐equatorial magnetosphere GOES 13 can measure in‐situ electron fluxes along a field line This technique shows a preliminary determination of the size of the loss cone